Colpodella sp. (Phylum Apicomplexa) Identified in Horses Shed Light on Its Potential Transmission and Zoonotic Pathogenicity - Xu, Ming; Hu, Yang; Qiu, Hongyu; Wang, Jingyuan; Jiang, Jiafu (Frontiers in Microbiology, 2022)
Colpodella species which mainly feed on protists and algae are free-living close relatives of apicomplexans and have been recently reported to cause red blood cell infection in an immunocompromised human host and in a tick-borne human infection resulting in neurological symptoms. Our molecular examination of piroplasmosis infecting horses in China, identified the nearly whole 18S rRNA gene sequences that are closely related to Colpodella sp. ATCC 50594 isolated from brown woodland soil at Gambrill State Park, shedding light on its potential across transmission and zoonotic pathogenicity.